Mengoptimalkan Faktor Diri dan Keluarga dalam Prestasi Akademik Remaja - Nuraini Novianti; Melly Latifah; Neti Hernawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
Academic achievement is influenced by many factors such as internal factor and external factor. Internal factors in this research is a factor that can be used to learn. Meanwhile, the external factor of the adolescent involved is the factor of the family in the form of parenting style that implements the parents. This study aims to analyze the nurturing style, motivation, and strategies in learning against adolescent achievement. The data were collected using a questionnaire technique involving 149 VIII students from two State Junior High Schools in Bogor. The results found that about nine of the adolescents perceived the authoritative parenting style (89,3%). The results of the study also found that more than half of adolescents had moderate motivation categories (53,0%) with broader motivation. Seven of the adolescents had a low learning strategy (72,3%) and a fairly well-done dimension was the regulatory effort. The academic achievement of adolescents is almost entirely (95,3%) is categorized well. Multiple linear regression models show that the duration of mother education and authoritarian parenting style have a significant negative effect on academic achievement. Meanwhile, the mother's authoritative parenting style and self-determination strategy in learning have a significant positive effect on academic achievement.